2011
DOI: 10.1128/iai.00881-10
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination againstChlamydiaGenital Infection Utilizing the MurineC. muridarumModel

Abstract: 2Chlamydia trachomatis genital infection is a worldwide public health problem, and considerable effort has been expended on developing an efficacious vaccine. The murine model of C. muridarum genital infection has been extremely useful for identification of protective immune responses and in vaccine development. Although a number of immunogenic antigens have been assessed for their ability to induce protection, the majority of studies have utilized the whole organism, the major outer membrane protein (MOMP), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(143 citation statements)
references
References 115 publications
(164 reference statements)
4
139
0
Order By: Relevance
“…Major outer membrane protein (MOMP) is the most abundant chlamydial protein constituting up to 60% of the EB dry weight. As well as being an immunodominant antigen, 7 it has been shown to induce protective immunity similar to that of live bacteria. 8 In recent years, aluminum salt adjuvants have been used as carriers for TLR agonists and immunomodulatory molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Major outer membrane protein (MOMP) is the most abundant chlamydial protein constituting up to 60% of the EB dry weight. As well as being an immunodominant antigen, 7 it has been shown to induce protective immunity similar to that of live bacteria. 8 In recent years, aluminum salt adjuvants have been used as carriers for TLR agonists and immunomodulatory molecules.…”
Section: Introductionmentioning
confidence: 99%
“…An adaptive immune response is then initiated via antigen-processing cells presenting chlamydial antigens to T cells in local lymph nodes. Animal studies (73)(74)(75)(76) and, to a certain degree, human studies (73)(74)(75)(76)(77)(78) have found that IFN-␥-producing T cells are essential for resolution of chlamydial infections (72,79,80).…”
Section: Pathogen Defence Via Ido (Indoleamine 23-dioxygenase)-mediamentioning
confidence: 99%
“…Moreover, it can cause hydrosalpinx, fibrosis, infertility, and abortion in mice (118)(119)(120)(121). C. muridarum genital infection is usually resolved in 3 to 4 weeks, and the mice are partially protected against subsequent reinfections (122,123). C. trachomatis is also used, but the infection in mice is less severe and is resolved more quickly than C. muridarum infection.…”
Section: Mousementioning
confidence: 99%